Digital Payment Systems A Way to Protect One Another From Coronavirus - Kaur, Gurleen; Kushwaha, Bijay Prasad (The journal of contemporary issues in business and government, 2021)
Every nations in this world is suffering from pandemic of COVID-19. COVID-19 started from Wuhan, China and now it is everywhere in the world. Social distance and hand-wash are two methods to prevent ourselves from this virus. The world is experience lockdown even though we are buying our daily needs and making payment for such items. Cash transfer process requires involvement of our hand to exchange and this process increases chances of spread of COVID-19. This study will explore the various expert’s advices and elaborate experiments on the process of spread of corona virus. This paper will also show how digital payment process prevent spread of contagious virus corona. The paper is literature based and findings have been made from secondary sources. The comments of doctors, experts, and scientists have been collected from new articles and websites. The finding of study shows the social distancing is best way to protect each other from COVID- 19 and digital payment helps us to maintain social distancing during purchasing.